QTL analysis of seed weight and seed dormancy in black gram (Vigna mungo [L.] Hepper) - Lomlek, Chalinee; Suamuang, Sunisa; Laosatit, Kularb; Tangphatsornruang, Sithichoke; Tanadul, Orn-uma; Somta, Prakit (Agriculture and Natural Resources, 2023)
Importance of the work: Black gram is a scientifically important orphan crop with little research published on the molecular breeding of this legume. Seed weight is a key trait contributing to seed yield. Seed dormancy can be exploited to reduce pre-harvest sprouting. Objectives: To identify the quantitative trait loci (QTLs) controlling black gram seed weight and seed dormancy. Materials & Methods: Two F2 populations developed from a cross between cultivated (Chai Nat 80 [CN80]) and wild black gram (PI213017 or TVnu1076) were grown under field conditions. The F2 populations were determined for seed weight and seed dormancy. Single nucleotide polymorphism-based linkage maps previously constructed for the two population were used for QTL analysis. Candidate genes were identified using the reference genome sequence of CN80. Results: The broad-sense heritability (h2 ) calculated for seed weight was 65.23–73.71%, while that for seed dormancy was 81.53–99.80%. In total, 10 QTLs on 7 linkage groups (LGs) were detected for seed weight and three QTLs on two LGs were detected for seed dormancy. Depending on the population, QTLs explained between 5.07% (qSd100wt7.1+) and 34.20% (qSd100wt10.2+) of the seed weight variation, and between 10.18% (qSdwa6.1-) and 43.81% (qSd100wt6.2-) of the seed dormancy variation. Candidate genes of various functions were identified for these two traits. Main finding: Novel QTLs and candidate genes controlling seed weight and seed dormancy were identified for black gram. One of the candidate genes, WVD2-LIKE 4 for seed weight, appeared to be an ortholog with a candidate gene for the same trait in mungbean.